FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN TERHADAP KOPI BUBUK DI KOTA PALEMBANG. - Lusia nargis (JURNAL KOMPETITIF, 2015)
ABSTRACT This study aims to find the factors that affect customer satisfaction with coffee in Palembang and know the level of customer satisfaction with coffee consumed in Palembang. The research was conducted in Palembang which took place in two places, JM Supermarket cabang Kenten and Diamond Supermarket determined by purposive sampling.The results of this study indicate that the factors that affect customer satisfaction with coffee that is based on the results of a factor analysis of the packaging, brand factors, aroma factors, price factors , factors of motivating and perception. The level of customer satisfaction with coffee in the city of Palembang is, of the 45 respondents, 19 (42.22%) were very satisfied, 15 people (33.33%) were satisfied and 11 (24.45%) were not satisfied . Keywords : consumer satisfaction, coffee, brand,aroma, price, motivating,and perception.